Desarrollo de una propuesta de un sistema de tratamiento de agua residual generada en un laboratorio de análisis fisicoquímico (2020)
This project sought to evaluate a proposed wastewater treatment system generated in a physicochemical analysis laboratory, for which the water balance of the laboratory was described, identifying the amount of samples that enter monthly equivalent to 2,2174 m3 of water to be disposed of monthly and through a characterization of these generated wastewater, four parameters were identified outside the permissible limits according to article 16 of resolution 0631 of 2015, which were BOD (135.1 mg O2 / L), COD (319 mg O2 / L), Total suspended solids (202.6 mg / L) and minimum pH (2.9). A bibliographic review was carried out to identify possible treatment options and by means of a selection matrix the use of a treatment system for the laboratory composed of a neutralization process and an electrocoagulator was determined, later the operational ranges of operation of both were theoretically defined. processes for parameters such as residence time of 5 to 10 minutes for neutralization and between 30 and 60 minutes for electrocoagulation, source voltage, use of Sodium Hydroxide as neutralizer, use of Iron and Aluminum electrodes, as well as sizing of both equipment required to handle a volume of water of 0.5544 m3, determining the repetition of the treatment four times per day of washing.